Psychopathy as Predictor of Cyberstalking among Youth - Naila Niaz; Dr. Sher Dil; Warda Sadiq (Indus Journal of Social Sciences, 2025)
Psychopathy as a part of dark triad and tetrad, has been linked with many problematic behaviors across lifespan. Research has identified psychopathy as predictor of criminal behavior and recidivism. The recent rise in the cyber communication or online communication, a related phenomenon of cyberstalking has been center of attention for the researchers. The purpose of the current study was to assess the causal relationship between psychopathy and cyberstalking. A purposively selected sample of 300 youth age range of 18-24 years were recruited from Hazara Division, who were enrolled in BS programs and identified themselves as involved in cyberstalking. Urdu psychopathy scale, cyberstalking scale along with demographic sheet were given to the participants after obtaining inform consent. The data analysis revealed a positive relationship between psychopathy and cyberstalking. Psychopathy significantly predicted the 22.2% variation in cyberstalking. Age had significant negative correlation with psychopathy and no significant relation cyberstalking. Results also revealed that males have significant higher levels of psychopathy and cyberstalking as compared to females. Hence study indicated that psychopathy predicted cyberstalking.